Amazing muslims who changed the world Extraordinary stories of incredible people - Islam, Burhana (London : Penguin random house UK, 2020)
The are many famous Muslims in this book - for example, Malala Yousafzai, Sir Mo Farah and Muhammad Ali. But there are many more Muslim people who have changed our world. From pirate queens and athletes to warriors and mathematicians, this book is about some of these amazing Muslims.
Keywords: English - Biography